The Opportunities and Challenges of Halal Tourism Industry in Indonesia: A SWOT Analysis - Azwar, Azwar; Abur Hamdi Usman; Khaerul Aqbar; Humaira Ahmad; Mutsalim Khareng (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
The rapid global growth of the tourism industry has positioned halal tourism as one of the most promising sectors in Muslim-majority countries. Indonesia, with its large Muslim population and rich natural and cultural diversity, holds significant potential to become a leading destination in the halal tourism market. This study aims to examine the opportunities and challenges faced by Indonesia’s halal tourism industry and to formulate strategic recommendations for its development. Employing a descriptive qualitative method with a phenomenological approach and SWOT analysis, this study explores internal and external factors influencing the industry. The findings reveal that Indonesia’s strengths lie in the growing Muslim population, increasing awareness of the halal lifestyle, and government support through institutional coordination. Meanwhile, the main challenges include relatively low-quality infrastructure compared to competitors, limited technological integration, and the absence of specific financial and legal frameworks for halal tourism. The study recommends a growth strategy through horizontal integration, emphasizing digital branding and social media promotion, as well as the urgency of establishing a national law on halal tourism. The novelty of this research lies in its comprehensive positioning of Indonesia’s halal tourism industry using SWOT analysis to bridge the gap between potential and policy direction, offering strategic insight for policymakers and industry stakeholders.